(untitled) (Italian Journal of Public Health, 2012)
Background: although the efficacy of pneumococcal vaccination for the more common serotypes of Streptococcus pneumoniae has been demonstrated, the 13-valent vaccine (Prevenar 13 ® ) is still offered in different ways in the Italian regional healthcare units, and in the region of campania, some local health authorities administer the vaccine free of charge whilst others practice a co-payment. MethodS: We performed a budget impact analysis of the possible free administration of Prevenar 13® vaccine to all newborns in the campania region, by comparing two different delivery settings, one having an active vaccination program and another in which such program was absent. during the operation of the vaccination program, the number of expected cases with 50, 80 and 100% vaccine coverage in the popula- tion was considered. the economic advantage resulting from pneumococcal diseases deemed avoidable thanks to the vaccination was compared with the costs of the vaccination program. the analysis considered the direct costs in the 2 years after implementation of the vaccination program. costs were expressed in € euros 2010. reSultS: although we did not consider the benefits achievable in the 10 years following the vaccina- tion, nor the herd effects, we showed that offering anti-pneumococcal vaccination to all newborns could give economic advantages to the region, estimated as close to 1 million euros. concluSIon: the use of Prevenar 13® can be considered a greatly advantageous public health strategy.